Combining ecological research with environmental education - Amos Bouskila (Environmental Association of Southern Africa, 1987)
The relationship between ecological research and environmental education prograllllleS at the Hazeva Field Study Centre in Israel is described. Mutual benefits to both researchers and students are discussed and the benefits to the environment outlined.